ANALISIS SENTIMEN PENGARUH PEMBELAJARAN DARING TERHADAP MOTIVASI BELAJAR DI MASA PANDEMI MENGGUNAKAN NAIVE BAYES DAN SVM - Ariansyah Ariansyah; Mira Kusmira (LPPM, 2021)
The COVID-19 pandemic in Indonesia has had a huge impact on the education sector. Where it is today, it must implement and adapt a new learning model called online. motivation in learning is very important because it can improve achievements. In this case there are many pros and cons about online learning, many people's opinions on social media, especially Twitter about the influence of online learning on learning motivation. This study aims to analyze the influence between online learning and learning motivation. Public opinion on Twitter is used as a sentiment analysis to find out what people think about online learning on learning motivations whether positive or negative. The data used are tweets in indonesian with the keywords